P17.03 Convenient hiv testing service models combined with rapid testing are attracting previously untested gay and bisexual men. (13th September 2015) - Knight, V; Wand, H; Gray, J; Keen, P; McNulty, A; Guy, R
Abstract : Introduction: HIV testing is a cornerstone of the treatment as prevention (TasP) approach. In Australia, gay and bisexual men (GBM) account for the majority of HIV diagnoses each year, but less than a quarter are testing at the recommended frequency. In response, a range of new service delivery models were introduced in Sydney over the past few years. We assessed which HIV testing service delivery models were more likely to attract GBM who had never previously tested or were testing infrequently. Methods: We compared demographics, risk behaviour and HIV testing history among new GBM clients attending three different HIV testing service models (fast-track Xpress clinic, fixed-site community-based service and time-limited community-based shopfront) between August 2013 and May 2014. All services offered HIV rapid testing. We used multivariate regression to assess factors (including service model) associated with being untested or infrequent testers (not tested within the past 12 months). Results: Overall, 1704 new GBM attended the services; 19% were untested and 41% were infrequent testers. Across the services, there were significant differences in demographics, risk behaviour and past HIV testing history. The overall HIV seropositivity was 1.2% (95% CI: 0.8%–1.9%) and STI positivity was 12.4% (95% CI: 11.6–17.2) with no significant differences across services. Factors independently associated with being untested were attendance at the two community sites, younger age, being born in Asia, living in North Sydney, being bisexual and reporting fewer male sexual partners. Factors independently associated with infrequent testers were attending the fast track Xpress clinic, being older, being born in Asia and reporting fewer male partners. Conclusion: The findings show the two community sites reached more untested men and the fast-track clinic model more infrequent testers but the HIV/STI diagnosis rate was consistent across services, indicating that all three testing models are important to increase HIV testing among GBM. Disclosure of interest statement: Vickie Knight is supported by an Australian Postgraduate Association scholarship. No pharmaceutical grants were received in the development of this study.